Metode Forward Chaining Untuk Mendiagnosa Penyakit Kanker Payudara - Santawali, Santawali (Forum Kerjasama Pendidikan Tinggi, 2019)
Cancer is a disease caused by abnormal growth of body tissue cells that turn into cancer cells. One of them is breast cancer, cancer is often suffered by women. Some women tend not to know it has been exposed to the disease. Expert systems are computer-based systems that use knowledge, facts and reasoning techniques in solving problems commonly solved by an expert. Expert system is an artificial intelligence that learns how to imitate the way an expert thinks in solving a problem, or take a decision based on existing facts. In this study, we will design an expert system used to diagnose cancer using forward chaining method. This expert system is used as an early diagnosis to know the stadium suffered by the patient and the solution